Ethics, ethnocentrism and social science research
1 online resource
Keywords: This book addresses the ethical and methodological issues that researchers face while conducting cross-cultural social research. With globalization and advanced means of communication and transportation, many researchers conduct research in cross-cultural, multicultural, and transnational settings. Through a range of case studies, and drawing on a range of disciplinary expertise, this book addresses the ethics, errors, and ethnocentrism of conducting law and crime related research in settings where power differences, as well as stereotypes, may come into play. Including chapters from scholars across cultures and settings - including Greece, Canada, Vienna, South Africa, India, and the United States - this book provides an invaluable survey of the issues attending cross-cultural social justice research today. Engaging issues confronted by all cross-cultural researchers this book will be invaluable to those working across the social sciences as well as professionals in criminal justice and social work.